Deduplication of Image at Client Side Using DICE Protocol - R, Akshay; AK, Ankith; B, Amith; R, Jayanth; Mensinkai, Kiran (International Journal of Computer Sciences and Engineering, 2025)
With the approach of distributed computing, verified information de-duplication has picked up a ton of fame. Numerous methods have been proposed in the writing of this continuous research territory. Among these procedures, theMessage Locked Encryption (MLE) conspire is regularly referenced. Analysts have presented MLE based conventions which give verified de-duplication of information, where the information is by and large in content structure. Thus, sight and sound information, for example, pictures and video, which are bigger in size contrasted with content documents, have not been given much consideration. Applying tied down information de-duplication to such information documents could essentially decrease the expense and space required for their capacity. In this paper we present a safe de-duplication conspire for close indistinguishable (CI) pictures utilizing the Dual Integrity Convergent Encryption (DICE) convention, which is a variation of the MLE based plan. In the proposed plan, a picture is disintegrated into squares and the DICE convention is connected on each square independently as opposed to on the whole picture. As a result, the hinders that are normal between at least two CI pictures are put away just once at the cloud.